ANALISIS SPASIAL PERUBAHAN TUTUPAN LAHAN DI DAS WAE BATUGANTONG, KOTA AMBON - Philia Christi Latue; Heinrich Rakuasa (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
The development of developed land over the last 15 years in Ambon City has affected land cover changes in the Wae Batutangan watershed. This is a result of higher population growth and the need for residential land, which is increasing every year. This study aimed to analyze land cover changes in the Wae Batu Hang watershed in 2012, 2017, and 2022. The method used in this study was a spatial comparison of land cover changes in 2012 and 2017, as well as in 2017 and 2022. Land cover data is obtained from the results of this study. Visual interpretation and digitization where land cover in 2012 was obtained from IKONOS images, and land cover in 2017 and 2022 were obtained from SPOT 6 images. Results of this study showed that the cover of built-up land and open land continues to increase in the area, along with population growth and the high demand for land in watersheds.